CP12 fine-tunes the Calvin-Benson cycle and carbohydrate metabolism in cyanobacteria - Lucius, Stefan; Theune, Marius; Arrivault, Stéphanie; Hildebrandt, Sarah; Mullineaux, Conrad W.; Gutekunst, Kirstin; Hagemann, Martin (Frontiers in Plant Science, 2022)
The regulatory protein CP12 can bind glyceraldehyde 3-phosphate dehydrogenase (GapDH) and phosphoribulokinase (PRK) in oxygenic phototrophs, thereby switching on and off the flux through the Calvin-Benson cycle (CBC) under light and dark conditions, respectively. However, it can be assumed that CP12 is also regulating CBC flux under further conditions associated with redox changes. To prove this hypothesis, the mutant Δcp12 of the model cyanobacterium Synechocystis sp. PCC 6803 was compared to wild type and different complementation strains. Fluorescence microscopy showed for the first time the in vivo kinetics of assembly and disassembly of the CP12-GapDH-PRK complex, which was absent in the mutant Δcp12. Metabolome analysis revealed differences in the contents of ribulose 1,5-bisphosphate and dihydroxyacetone phosphate, the products of the CP12-regulated enzymes GapDH and PRK, between wild type and mutant Δcp12 under changing CO2 conditions. Growth of Δcp12 was not affected at constant light under different inorganic carbon conditions, however, the addition of glucose inhibited growth in darkness as well as under diurnal conditions. The growth defect in the presence of glucose is associated with the inability of Δcp12 to utilize external glucose. These phenotypes could be complemented by ectopic expression of the native CP12 protein, however, expression of CP12 variants with missing redox-sensitive cysteine pairs only partly restored the growth with glucose. These experiments indicated that the loss of GapDH-inhibition via CP12 is more critical than PRK association. Measurements of the NAD(P)H oxidation revealed an impairment of light intensity-dependent redox state regulation in Δcp12. Collectively, our results indicate that CP12-dependent regulation of the CBC is crucial for metabolic adjustment under conditions leading to redox changes such as diurnal conditions, glucose addition, and different CO2 conditions in cyanobacteria.